Evolucion de razas de Hemileia vastatrix en Colombia - Cristancho A, M.=700 1 Escobar O, C.
(En, Es)
ilus., 29 ref.
Keywords: HEMILEIA VASTATRIX; PATOGENICIDAD; MORBOSIDAD; ROYA; VARIACION GENETICA; ADN; RIBOSOMAS; MARCADORES GENETICOS; COLOMBIA; CENICAFE